PEMANFAATAN INSTAGRAM SEBAGAI MEDIA PROMOSI PADA MENDOAN OM NDUT - Debby Kurniadi; Nikita Putriana Ananta (JURNAL SOSIO-KOMUNIKA, 2023)
The Covid-19 pandemic in Indonesia has passed, but its impact can still be felt. Likewise with MSMEs in the city of Pekanbaru, feeling the impact of the decline in customers causing decreased turnover. However, Mendoan Om Ndut's business at the Tugu Keris Round about tour was able to survive and was able to overcome this problem by carrying out promotional activities on Instagram using the services of influencers. The purpose of this research is to find out how effective Instagram is as a medium for promoting Mendoan Om Ndut's business and to find out whether there are factors that become obstacles in promoting Mendoan Om Ndut's business on Instagram. This study used qualitative research methods. Based on the results of this study, the success of Instagram in promoting the Mendoan Om Ndut business is through experiential marketing strategies, namely sense, feel, think, action and relation. Supported by the results of interviews with researchers, it can be seen that promotions on Instagram are very effective, so that the Mendoan Om Ndut business can survive. Mendoan Om Ndut experienced a significant increase in subscribers and turnover, currently Mendoan Om Ndut has experienced business stability to date.